2017
DOI: 10.1038/s41598-017-09365-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral properties of resveratrol against pseudorabies virus are associated with the inhibition of IκB kinase activation

Abstract: Pseudorabies virus (PRV) is a pathogen of swine resulting in devastating disease and economic losses worldwide. Resveratrol (Res) exhibits inhibitory activity against a wide range of viruses. Despite these important advances, the molecular mechanism(s) by which Res exerts its broad biological effects have not yet been elucidated. In this paper, the antiviral activity of Res against PRV and its mechanism of action were investigated. The results showed that Res potently inhibited PRV replication in a dose-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 40 publications
2
57
0
Order By: Relevance
“…HO-1-derived CO was also indicated to play a key role in the antiviral activity of HO-1, whereby CO scavenger Hb partially reversed the inhibitory effect of CoPP-induced HO-1 on PRV replication. Previous studies have demonstrated that CO decreases the replication ability of PRRSV by suppressing the activation of the NF-κB signaling pathway, which plays a significant role in PRV replication Zhao et al, 2017). Thus, the NF-κB signaling pathway may act as a potential target for the HO-1/CO system to exert its antiviral effect.…”
Section: Discussionmentioning
confidence: 98%
“…HO-1-derived CO was also indicated to play a key role in the antiviral activity of HO-1, whereby CO scavenger Hb partially reversed the inhibitory effect of CoPP-induced HO-1 on PRV replication. Previous studies have demonstrated that CO decreases the replication ability of PRRSV by suppressing the activation of the NF-κB signaling pathway, which plays a significant role in PRV replication Zhao et al, 2017). Thus, the NF-κB signaling pathway may act as a potential target for the HO-1/CO system to exert its antiviral effect.…”
Section: Discussionmentioning
confidence: 98%
“…Some dietary polyphenols (e.g., quercetin, resveratrol, rutin) show a certain efficacy against leishmaniosis [90], and giardiasis [91]; furthermore, resveratrol itself has been suggested as a potential restorative agent against toxoplasmosis brain disorders [92] and Schistosoma mansoni infections [93]. As far as the effects on viruses, human and animal evidence suggest polyphenolic compounds (e.g., resveratrol, tea polyphenols) possess potential preventive and therapeutic effects, and might be used as adjuvant therapy for the management of viral infection, e.g., influenza, herpes simplex, pseudorabies, hepatitis C, porcine reproductive and respiratory syndrome, and even Ebola [88,[94][95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, overactivation of the NF-κB and MAPKs pathways were observed in LPS-induced inflammation (7,21). NF-κB, a critical regulator of cytokine production, cell activation and proliferation, serves an important role in regulating inflammation and immune responses to extracellular stimulus (22).…”
Section: Discussionmentioning
confidence: 99%